Love the sin : sexual regulation and the limits of religious tolerance - Jakobsen, Janet R., 1960- (Sexual cultures., 2003)
Sex. Religion. There is no denying that these two subjects are among the most provocative in American public life. Even the constitutional principle of church-state separation seems to give way when it comes to sex: the Supreme Court draws on theology as readily as it draws on case law when rendering decisions that touch on sexuality. In this compelling and carefully argued study, Janet R. Jakobsen and Ann Pellegrini examine this powerful and disturbing connection as they explore the reasons why secular institutions habitually use religion to regulate sexual life. From state legislatures to the halls of Congress and the Supreme Court, from daily newspapers to popular magazines and television talk shows, Jakobsen and Pellegrini illustrate the intensity of America's obsession with sex in the name of values and the dangers it poses to some of our most basic freedoms. Using a wide range of case studies, Love the Sin offers an insightful critique of the ways in which sexuality in general and homosexuality in particular are discussed and debated in the public arena. Additionally, the book sets forth constructive alternatives that highlight the vital links between sexual and religious freedom and expose the hazards of using religion as a justification for regulating sexuality. A timely, necessary, and refreshing contribution to the many debates surrounding religion, morality, and sex, Love the Sin boldly dreams an America that lives up to its promise of freedom and justice for all.